ANTIMYCOBACTERIAL COMPOUNDS FROM NASTURTIUM OFFICINALE - Quezada-Lázaro, RodrÃgo; Fernández-Zuñiga, Eunice A; GarcÃa, Abraham; Garza-González, Elvira; Alvarez, Laura; Camacho-Corona, Maria del Rayo (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Nasturtium officinale is a plant used in Mexican traditional medicine to treat respiratory infections such as tuberculosis. In previous studies, it was found that the chloroform extract of the aerial parts of N. officinale showed good activity against one sensitive and four drug-resistant Mycobacterium tuberculosis H37Rv strains. Therefore, the present research was focused on the fractionation and identification of the antimycobacterial principles of this species. Material and Methods: The chloroform extract was prepared and fractionated by column chromatography using silica gel and gradient of chloroform/methanol, yielding 14 fractions. Each fraction was analyzed by thin-layer chlromatography under UV light. The obtained fractions were further tested against Mycobacterium tuberculosis H37Rv strain using Alamar blue microassay. Results: Of the 14 fractions assayed, only fractions 3 to 5 showed good inhibitory activity against M. tuberculosis H37Rv. The chemical composition of three fractions by GC-MS led to the identification of E-phytol as the most abundant and common component. Conclusion: Antimycobacterial properties of the three active fractions were attributed to E-phytol and palmitic acid.